Role of Extracellular Vesicles in Autoimmune Pathogenesis - Wu, Wen-Cheng; Song, Sheng-Jiao; Zhang, Yuan; Li, Xing (Frontiers in Immunology, 2020)
Autoimmune diseases are conditions that emerge from abnormal immune responses to natural parts of the body. Extracellular vesicles (EVs) are membranous structures found in almost all types of cells. Because EVs often transport “cargo” between cells, their ability to crosstalk may be an important communication pathway within the body. The pathophysiological role of EVs is increasingly recognized in autoimmune diseases, including multiple sclerosis, rheumatoid arthritis, systemic lupus erythematosus, Sjogren's syndrome, Type 1 diabetes, and autoimmune thyroid disease. EVs are considered as biomarkers of these diseases. This article outlines existing knowledge on the biogenesis of EVs, their role as messegers in cellular communication and the function in T/B cell differentiation and maturation, and focusing on their potential application in autoimmune diseases.